The Mechanism of Incorporation the Treaty and its Legal Value into Iraqi Law - Saleem, Shams Jamal Saleem; Almaliky, Hadi (Journal of Legal Sciences, 2023)
The importance of international treaties reside at the present time in regulating a several issues within the internal scope of the state, and that after it was monopolized by the internal legal system of the latter, besides this the three authorities of the state assume the task of implementing the obligations imposed by international treaties on the states party to them.      Therefore, we will expose in this study the mechanism used by the Iraqi state in incorporation the international obligations into the Iraqi internal legal system under the successive constitutions from the establishment of the Iraqi state until the issuance of the constitution (2005) in effect, as Iraq followed the approach of indirect incorporation of international treaties, which made the legal value of the international treaty Inferior to the constitution and equal to the legal value of ordinary Iraqi legislation.